Perceptions of Primary Healthcare Practitioners on the Effectiveness of Electronic Health Records Systems for Decision Support in Tanzania - Mwogosi, Augustino; Kibusi, Stephen; Shao, Deo (Journal of Health Informatics in Africa, 2024)
Background and Purpose: This study aims to examine the perceptions of primary healthcare practitioners on the effectiveness of Electronic Health Records (EHR) systems in providing decision support in Tanzania. Methods: The study employs a quantitative research approach, utilizing surveys and structured observations to collect data from healthcare practitioners in PHC settings. Descriptive statistical analysis is conducted to assess the functionalities and utilization of EHR systems. Results: The findings reveal that while EHR systems in PHC facilities offer certain benefits, such as facilitating access to patient information and improving administrative processes, there are limitations in their ability to support decision-making tasks effectively. Specific areas for improvement are identified, highlighting the need for targeted interventions to enhance the functionality of EHR systems in PHC settings. Conclusions: This study underscores the importance of addressing the identified limitations in EHR systems to optimize their effectiveness in supporting decision-making tasks in PHC settings in Tanzania. Targeted interventions are essential to enhance EHR functionality and improve healthcare delivery outcomes.